Mangrove Transplantation to the North: Carbon Sequestration Capacity—Drivers and Strategies - Kewei Zhou; Yujuan Lv; Yang Gong; Jing Su; Lei Wang; Shengmin Wu; Xi Lin; Qiuying Lai; Yixin Xu; Xingyi Duan (Journal of Marine Science and Engineering, 2025)
Mangroves play a pivotal role in carbon sequestration. To investigate the characteristics and driving factors of carbon sequestration in planted mangrove forests, we focused on planted mangrove forests in Wenzhou City, Zhejiang Province, China. Through a statistical analysis of soil physicochemical properties and plant morphological characteristics, we assessed carbon stock distribution patterns and identified key influencing factors, providing scientific support for the northward expansion of mangroves. The results demonstrated significant differences in soil properties and plant morphological characteristics among different stands (p